Allure of the Moroccan caftan exhibit installation - Unidentified photographer (Colorado State University. Libraries, 2017)
Photograph of caftans in the exhibit installation “The Allure of the Moroccan Caftan,” held in The Richard Blackwell Gallery in the fall of 2017. A violet caftan with embroidery down the length of the front is positioned on a standing mannequin. A white caftan with blue embroidery along the next is positioned on a seated mannequin.
Keywords: Fashion -- History; Fashion -- Exhibitions